The Ischemic Environment Drives Microglia and Macrophage Function - Fumagalli, Stefano; Perego, Carlo; Pischiutta, Francesca; Zanier, Elisa R.; De Simoni, Maria-Grazia (Frontiers in Neurology, 2015)
Cells of myeloid origin such as microglia and macrophages act at the crossroads of several inflammatory mechanisms during pathophysiology. Besides pro-inflammatory activity (M1 polarization), myeloid cells acquire protective functions (M2) and participate in the neuroprotective innate mechanisms after brain injury. Experimental research is making considerable efforts to understand the rules that regulate the balance between toxic and protective brain innate immunity. Environmental changes affects microglia/macrophage functions. Hypoxia can affect myeloid cell distribution, activity and phenotype. With their intrinsic differences, microglia and macrophages respond differently to hypoxia, the former depending on ATP to activate, the latter switching to anaerobic metabolism and adapting to hypoxia. Myeloid cell functions include homeostasis control, damage-sensing activity, chemotaxis and phagocytosis, all distinctive features of these cells. Specific markers and morphologies enable to recognize each functional state. To ensure homeostasis and activate when needed, microglia/macrophage physiology is finely tuned. Microglia are controlled by several neuron-derived components, including contact-dependent inhibitory signals and soluble molecules. Changes in this control can cause chronic activation or priming with specific functional consequences. Strategies such as stem cell treatment may enhance microglia protective polarization. This review presents data from the literature that has greatly advanced our understanding of myeloid cell action in brain injury. We discuss the selective responses of microglia and macrophages to hypoxia after stroke and review relevant markers with the aim of defining the different subpopulations of myeloid cells that are recruited to the injured site. We also cover the functional consequences of chronically active microglia and review pivotal works on microglia regulation that offer new therapeutic possibilities for acute brain injury.